Kinerja Keuangan Daerah Kabupaten / Kota Sebelum dan Setelah Pemekaran Daerah Sumatera Selatan - Benta Palantama Putra; Retno Ulfayatun Hidayah (COSTING : Journal of Economic, Business and Accounting, 2020)
In line with the spirit of regional autonomy, regional performance is measured through the ability of the region to manage and manage its own households. This study aims to analyze the financial performance of district / city areas before and after the division of regions in southern Sumatra. This type of research used in this research is quantitative descriptive. The sampling technique used was purposive sampling with a number of 6 parent districts experiencing expansion in the South Sumatra region. Data were analyzed in this test using t test (paired t-test). The results of this study indicate that: 1) measured from the fiscal decentralization ratio there are differences in the financial performance of the district government before and after the division in South Sumatra Province because the Total Local Revenue (PAD) has increased after the division; 2) measured from the ratio of capital expenditure harmony there are differences in the financial performance of district governments before and after the division in South Sumatra Province because capital expenditure (development) has increased after the division; 3) measured from the growth ratio of PAD there is no difference in the financial performance of district governments before and after the division in South Sumatra Province because the Regional Original Revenue (PAD) has not changed; 4) measured from the ratio of regional financial dependency there is no difference in the financial performance of the district government before and after the division in South Sumatra Province because the transfer revenue with total regional income has not changed. Keywords : Financial Performance, Regional Expansion,